Improving Psychomotor Skills of Fashion Design Students through Project-Based Learning in Knitting Technique Material - Rahmawati, Ika Prastiana; Miftahurrizqi, Miftahurrizqi; Tiantono, Muna Sri; Anggrainy, Silvya; Ni’mah, Siti Nazilatun; Tri Rahayu, Imami Arum; Mustofani, Heni; Nugroho, Yuli Sutoto (Indonesia Emerging Literacy Education, 2025)
Objective: This research investigates how applying the Project-Based Learning (PjBL) approach affects students’ cognitive performance in the subject of product creation using knitting techniques in Grade XI Fashion Design at VHS 8 Surabaya. Method: This The study utilized the Classroom Action Research (CAR) approach, conducted across three cycles that included the stages of planning, execution, observation, and reflection. Data collection was carried out through observational methods and performance-based assessments. The data were then analyzed using descriptive quantitative methods to evaluate the effectiveness of the learning implementation and the enhancement of students’ psychomotor skills. Results: The findings indicated that the application of the PjBL model was rated as “Good,” covering both student and teacher activities in collaboratively designing, conducting, and evaluating the project. Students’ psychomotor learning outcomes significantly improved, with average scores increasing from 77.5 in Cycle I to 87.5 in Cycle III. The student passing rate also rose markedly, from 15.6% to 87.5%. Novelty: What sets this research apart is its contextual emphasis on knitting techniques in the fashion domain, highlighting psychomotor skills—an element that has frequently been neglected in earlier studies. Moreover, this study reinforces the relevance of the PjBL model in supporting the Merdeka Curriculum, which emphasizes the strengthening of technical skills, student independence, and creativity in vocational education.